2022
DOI: 10.1007/978-3-030-94972-3_4
|View full text |Cite
|
Sign up to set email alerts
|

Context Matters: The Varying Roles of Social Ties for Professional Careers of Immigrants’ Descendants

Abstract: Research on social networks of immigrants and their descendants usually starts from the distinction between ‘ethnic’ ties and ties to members of the population without migration background. In migration studies ‘ethnic’ ties are repeatedly associated with ‘strong ties’, whereas ‘weak ties’ – that are found to be essential for the access to jobs in the wider society – are associated with contacts to members of the ‘majority population’. Building on existing criticism of this narrowing dichotomy and looking at u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Migrating to Germany as a child, he had to endure some difficulties including not always getting selected for teams at school or some unhelpful teachers. Nonetheless, he was enrolled at a university to study law which is acknowledged to be a difficult and highly-selective trajectory (see the chapter by Lang, Pott & Schneider, 2022 in this book, for the educational context of law studies in Germany). At the time of the interview, he was getting ready for his last chance to take the state exam with the aim to become a lawyer, which he found very difficult and time-intensive education.…”
Section: Bora: Nilgün's Sonmentioning
confidence: 99%
See 1 more Smart Citation
“…Migrating to Germany as a child, he had to endure some difficulties including not always getting selected for teams at school or some unhelpful teachers. Nonetheless, he was enrolled at a university to study law which is acknowledged to be a difficult and highly-selective trajectory (see the chapter by Lang, Pott & Schneider, 2022 in this book, for the educational context of law studies in Germany). At the time of the interview, he was getting ready for his last chance to take the state exam with the aim to become a lawyer, which he found very difficult and time-intensive education.…”
Section: Bora: Nilgün's Sonmentioning
confidence: 99%
“…As previous studies show, a degree in law in Germany is quite difficult achieve as well as to find a job due to an implicit expectation of an upper middle-class background (e.g. Lang et al, 2022).…”
Section: Bora: Nilgün's Sonmentioning
confidence: 99%
“…Further, we assume that specific resources related to one's 'migration background' may also become relevant for professional trajectories such as language skills, cultural competences or social capital in relation to the 'ethnic community' (Lang et al, 2018;Nohl et al, 2014;Schmidtke, 2010). For example, the social capital that descendants of migrants rely on when pursuing careers in fields where they frequently interact with immigrant clients is different from the social capital required for building connections in fields where they primarily deal with fellow professionals and clients without a migration background − yet both types of social capital are relevant in their careers (Lang et al, 2022;Keskiner & Waldring, 2022).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Comparing highly-skilled migrant descendants across the business, law and education sectors in Paris, Keskiner and Crul (2017) have shown that each sector values different forms of capital for reaching high status positions. Similarly, when investigating the access of immigrant descendants to positions in the fields of law and public administration in Germany, Lang et al (2022), illustrated the varying significance of 'ethnic' or 'cross-ethnic' forms of social capital.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation